PLAG1 immunohistochemistry is a sensitive marker for pleomorphic adenoma: a comparative study with PLAG1 genetic abnormalities. Issue 2 (19th October 2017) - Katabi, Nora; Xu, Bin; Jungbluth, Achim A; Zhang, Lei; Shao, Sung Y; Lane, Jason; Ghossein, Ronald; Antonescu, Cristina R
Abstract : Aims: Pleomorphic adenoma gene 1 ( PLAG1 ) gene rearrangement is the most common genetic abnormality in pleomorphic adenoma (PA), resulting in overexpression of PLAG1 protein. PA and carcinoma ex pleomorphic adenoma (CA ex‐PA) can mimic various benign and malignant salivary gland tumours. The aims of this study are to evaluate the sensitivity and specificity of PLAG1 immunohistochemistry (IHC) in the differential diagnosis of PA and CA ex‐PA and to compare the PLAG1 immunohistochemical results to PLAG1 gene abnormalities as detected by fluorescence in‐situ hybridisation (FISH). Methods and results: PLAG1 immunostaining was performed on 83 salivary gland tumours, including 23 PA, 15 CA ex‐PA and 45 other salivary gland tumours. In addition, PLAG1 FISH was performed in 44 cases for the presence of gene rearrangements/amplifications. The results showed high sensitivity of PLAG1 IHC in 96% of PA; however, discordant results between PLAG1 FISH abnormalities and IHC were noted in 15 of 44 cases (34%). Seven PA, four de‐novo myoepithelial carcinomas and one basal cell adenocarcinoma had negative FISH results, but were positive for IHC; while three salivary duct carcinomas (SDC) ex‐PA were positive for FISH but negative for IHC. PLAG1 IHC can differentiate CA ex‐PA from de‐novo SDC ( P = 0.02), but not from de‐novo myoepithelial carcinoma. PLAG1 IHC is a sensitive marker for PA. This could be due to PLAG1 gene abnormalities beyond FISH resolution. Conclusions: A negative PLAG1 IHC might be helpful in excluding a PA diagnosis. Interestingly, in the context of CA ex‐PA, FISH is more sensitive than IHC in detecting PLAG1 abnormalities.